Banality and custom of drug dealing violence in Rincón Grande de Pavas? - Umaña González, Carlos Andrés (2023)
Introduction: Recent research in the field of Social Sciences has shown the increase in the dynamics of drug retail in various neighborhood areas of the Greater Metropolitan Area. This scenario allows the investigation of various elements that occur within the dynamics linked to the sale and consumption of drugs, as well as the way in which these impact the communities in which they are located. Objective: Therefore, the current article aims to describe and explore two of the possible elements of the community-retail relationship: the banalization and the custom of violence, in a particular space that has been affected by the effects of drug retail for three decades: Rincón Grande in the Pavas district. Method: The methodology used is of a narrative nature, comprising a total of nine interviews and four face-to-face tours to different parts of the sector under study. Results:  As a result, there are various versions of neighbors in the area that allow us to reflect on the tension between custom and the banalization of violence as an effect of the repetition of drug violence, the violent constitution of the mortified community and alternatives to resignation. Conclusion: Based on these results, it is concluded that the narrative of the interviewees presents a fluctuation between forms of banalization of violence and versions that appeal to the otherness of the situation.